(untitled) (Research, Society and Development, 2021)
The peanuts (Arachis hypogaea L.) are one of the most cultivated oilseeds in the world, native to South America and belonging to the Fabaceae family. It is a crop that develops well in different conditions of temperature, climate and soil, so it is considered a rustic plant, but requires specific care to obtain good productivity. The crop is of great economic importance because it is directly linked to the industry, has high nutritional value, with a composition rich in oil and proteins. Soon it is used for several purposes, from natural consumption, toast, confectionery, as in the food industry where pasta is made, oil extraction or even for the production of bran, destined for animal feed. Peanut cultivation is done all over Brazil. The Southeast region stands out for being the largest producer, with São Paulo as the largest producing state. This way, the concentration of studies is directed to these areas, as well as in the Northeast region, where the cultivation is done in dry conditions. Considering the observed aspects, this work was developed with the objective of presenting a literature review, because it is fundamental to help readers with appropriate information, for consequent improvement in the production of this culture.